L’ironie à contretemps chez Annie Ernaux - Frédéric Martin-Achard (Contextes, 2025)
Using the work of Annie Ernaux as an example, this article focuses on two important features of class migrant narratives: the importance of metadiscourse and the issue of irony. While irony’s rejection, asserted in A Man’s Place and subsequently taken up again, is constitutive of Ernaux’s ethos, it reappears in The Years. The article examines the stylistic modalities of this return and questions its causes, hypothesising that an ironic temptation runs through Ernaux's work. It puts forward the hypothesis that irony in Ernaux's writings always works at cross-purposes. It is rejected in the 1980s and 1990s, while critics see it as a dominant aesthetic value, but it is practised in the 2000s, at a time when it may be declining in favour of empathy. It concludes that Ernaux’s position perhaps condemn class migrant narratives after her to a problematic relationship with irony.